2017
DOI: 10.17582/journal.aavs/2017/5.12.486.490
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Brucella Antibodies in Sheep with Special Aspect of Clinicalstatus and Breed

Abstract: | Brucellosis is an important zoonosis and a significant cause of reproductive losses in animals. To ascertain the serological status of the disease, a total of 1373 samples were screened for the presence of Brucella antibodies by RBPT and i-ELISA. Overall seroprevalence recorded in sheep was 6.84% (94 samples out of 1373) and 4.80% (66 out of 1373) by RBPT and i-ELISA respectively. Clinical status wise seroprevalence was recorded in heifer 4.65% and 6.97%, clinically healthy animals 2.62% and 1.79%,animals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Other authors have found breed differences in the prevalence of Brucella sp. antibodies in indigenous sheep (Mahboub et al, 2013;Patel et al, 2017;Shuaiband Mansour, 2018). These discrepancies in seroprevalence between breeds could be related to genetic variation involved in host resistance (Bishop, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Other authors have found breed differences in the prevalence of Brucella sp. antibodies in indigenous sheep (Mahboub et al, 2013;Patel et al, 2017;Shuaiband Mansour, 2018). These discrepancies in seroprevalence between breeds could be related to genetic variation involved in host resistance (Bishop, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Different species of Brucella tend to be hostspecific.Brucellae aregram-negative coccobacilli with straight or slightly curved, facultative intracellular,nonspore forming, non-motile, and non-capsulated cells (Waringa et al, 2016;Patel et al, 2017). Out of twelve species, the most implicated agents of brucellosis are B.abortus, B. melitensis, B. bovis, B.canis, and B.suis (Scholz et al, 2016;Sabrina et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Brucellae are gram-negative coccobacilli or short rods, facultative intracellular, non -motile, nonspore forming, urease + ive, Brucella members are aerobic, but some strains require an atmosphere containing 5 to 10% Co2 added for growth, especially on primary isolation and non-capsulated [13,14].Currently, there are eleven species described in the genus Brucella, every one may infect different host species, but each Brucella species has a favorite for its host species. Six classical out of eleven species include Brucella abortus, Brucella melitensis, Brucella ovis, Brucella canis, Brucella suis, Brucella neotomae and five novel species of BrucellaincludeBrucellaceti,Brucellapinnipedialis,Brucellamicroti,Brucellainopinata,Brucel la papionis [15][16][17].…”
Section: Introductionmentioning
confidence: 99%